2018
DOI: 10.7861/futurehosp.5-1-47
|View full text |Cite
|
Sign up to set email alerts
|

Clinician-directed improvement in the accuracy of hospital clinical coding

Abstract: Payment by results' (PbR) remuneration for healthcare services relies on the accurate conversion of diagnoses into Healthcare Resource Group (HRG) codes that are then reimbursed. Inconsistencies in documentation can result in inaccuracies in this process, with consequent implications for measuring activity, disease incidence and organisational performance. The aim of this study was to determine if clinician involvement increases accuracy in the coding of medical cases. Selected records of medical patients admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Not only does the coding team benefit from the knowledge of the clinician, but the doctor also learns about the coding process, allowing them to improve their documentation appropriately in the future. 11 Another previous study from Joose, dkk showed that a dedicated course on injury coding using the AIS98 significantly improved the overall percentage of correctly coded injuries and correctly assigned injury severity at the Trauma Centre Brabant in the Netherlands. The learning effect of a course seems to last, as the results of this study showed improved performance scores until six weeks after the course.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Not only does the coding team benefit from the knowledge of the clinician, but the doctor also learns about the coding process, allowing them to improve their documentation appropriately in the future. 11 Another previous study from Joose, dkk showed that a dedicated course on injury coding using the AIS98 significantly improved the overall percentage of correctly coded injuries and correctly assigned injury severity at the Trauma Centre Brabant in the Netherlands. The learning effect of a course seems to last, as the results of this study showed improved performance scores until six weeks after the course.…”
Section: Resultsmentioning
confidence: 95%
“…This resulted in a higher remuneration equating to an increase of £318 per patient. 11 Other than good documentation; good communication and understanding between all health professions in the hospital also played a role in increasing the accuracy of the codes. In the hospital setting, the role of improving health and function is shared across all health professionals of the aim of successful discharge and reduced admissions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 10 11 However, there has been a focus on coder-coder and clinician-coder auditing, with some arguing that collaborative efforts should be led by senior clinicians as opposed to junior doctors. 6 We sought to establish whether medical student-led auditing could improve the accuracy of coding, thereby improving discharge summaries and generating income for the trust.…”
Section: Open Accessmentioning
confidence: 99%
“…There is an example of a simple but elegant service redesign project to maintain equity of care, 7 educational initiatives to support the transition from medical student to foundation year doctors 8 and important lessons regarding clinical engagement in coding. 9 Early this year we will start to be listed on PubMed Central, which should also encourage those who want to ensure their research reaches the widest possible audience.…”
mentioning
confidence: 99%